Learning or inertia? The impact of experience and knowledge codification on post-acquisition integration - Castellaneta,F; Valentini,G; Zollo,M (Industrial and Corporate Change, 2018)
© The Author 2017. Published by Oxford University Press on behalf of Associazione ICC. All rights reserved. This article develops and tests a theory on the evolution of complex organizational decisions, such as the decision to integrate (or not) a target company during the post-acquisition management phase. Using a sample of US bank mergers, we show that persistence in-or variation of-integration decisions depends on two key factors: integration experience and related knowledge codification. Integration experience tends to generate persistence in the integration decision, which is associated with poor deal performance. Moreover, we show that when knowledge codification is low, the persistence caused by integration experience further increases. However, when knowledge codification is sufficiently high, the inertial effect of experience diminishes significantly. Hence, high levels of knowledge codification can weaken the effects of decision inertia, which suggests that as knowledge codification increases, the role of knowledge codification switches from strengthening inertia to promoting learning.